Association of Endogenous Erythropoietin Levels and Iron Status With Cognitive Functioning in the General Population - Ayerdem, Gizem; Bosma, Matthijs J.; Vinke, Joanna Sophia J.; Ziengs, Aaltje L.; Potgieser, Adriaan R. E.; Gansevoort, Ron T.; Bakker, Stephan J. L.; De Borst, Martin H.; Eisenga, Michele F. (Frontiers in Aging Neuroscience, 2022)
Background: Emerging data suggest that erythropoietin (EPO) promotes neural plasticity and that iron homeostasis is needed to maintain normal physiological brain function. Cognitive functioning could therefore be influenced by endogenous EPO levels and disturbances in iron status. Objective: To determine whether endogenous EPO levels and disturbances in iron status are associated with alterations in cognitive functioning in the general population. Materials and methods: Community-dwelling individuals from the Prevention of Renal and Vascular End-Stage Disease (PREVEND) study, a general population-based cohort in Groningen, The Netherlands, were surveyed between 2003 and 2006. Additionally, endogenous EPO levels and iron status, consisting of serum iron, transferrin, ferritin, and transferrin saturation were analyzed. Cognitive function was assessed by scores on the Ruff Figural Fluency Test (RFFT), as a reflection of executive function, and the Visual Association Test (VAT), as a reflection of associative memory. Results: Among 851 participants (57% males; mean age 60 ± 13 years), a higher endogenous EPO levels were independently associated with an improved cognitive function, reflected by RFFT scores (P<0.001). In multivariable backward linear regression analysis, EPO levels were among the most important modifiable determinants of RFFT scores (ß=0.08, P=0.005), but not of VAT scores. Of the iron status parameters, only serum ferritin levels were inversely associated with cognitive function, reflected by VAT scores, in multivariable logistic regression analysis (odds ratio, 0.66; 95% confidence interval 0.56 – 0.77; P<0.001 for high performance on VAT, i.e., ≥ 11 points). No association between iron status parameters and RFFT scores was identified. Conclusion: The findings suggest that endogenous EPO levels and serum ferritin levels are associated with specific cognitive functioning tests in the general population. Higher EPO levels are associated with better RFFT scores, implying better executive function. Serum ferritin levels, but not other iron status parameters, were inversely associated with high performance on the VAT score, implying a reduced ability to create new memories and recall recent past. Further research is warranted to unravel underlying mechanisms and possible benefits of therapeutic interventions.